Approach and initial treatment of the traumatized chest in the Emergency - Bonilla, Conrado (Cirugía del Uruguay, 1990)
Very often we are almost always in front of polytrauma and chest trauma in these patients run the risk of being misunderstood and often misdiagnosed. The combination of lesions in the different noble parenchyma they are particularly dangerous.